2017
DOI: 10.1039/c7cc02247f
|View full text |Cite
|
Sign up to set email alerts
|

Targeted cancer imaging and photothermal therapy via monosaccharide-imprinted gold nanorods

Abstract: Plasmonic nanomaterials have been widely used for photothermal therapy (PTT) of cancer, but their recognition specificity remains challenging. We prepared monosaccharide-imprinted gold nanorods (AuNRs) for targeted cancer PTT, using sialic acid (SA) as a representative monosaccharide. The SA-imprinted AuNRs exhibited good specificity, enabling the killing of cancer cells without damaging healthy cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(93 citation statements)
references
References 47 publications
2
89
0
2
Order By: Relevance
“…Interestingly, it has been reported that constructs based on gold nanorods exhibit nearly twofold higher signal‐to‐noise ratio than constructs based on gold nanospheres . Furthermore, because gold nanorods absorb near‐infrared light, they have been widely used in the literature for photothermal therapy, making them candidates for use in theranostic platforms …”
Section: Hybridization‐based Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been reported that constructs based on gold nanorods exhibit nearly twofold higher signal‐to‐noise ratio than constructs based on gold nanospheres . Furthermore, because gold nanorods absorb near‐infrared light, they have been widely used in the literature for photothermal therapy, making them candidates for use in theranostic platforms …”
Section: Hybridization‐based Probesmentioning
confidence: 99%
“…[194] Furthermore, because gold nanorods absorb near-infrared light, they have been widely used in the literature for photothermal therapy, making them candidates for use in theranostic platforms. [195][196][197] In a strategy analogous to that used with spherical gold NP-MBs, Wang et al used gold nanorod MBs for detection of Dll4 mRNA in HUVEC cells. [194] Importantly, they were able to track Dll4 mRNA and study its dynamics in individual cells.…”
Section: Gold Nanoparticle Basedmentioning
confidence: 99%
“…MIPs have found important applications in many areas,s uch as separation, [16] sensing, [17] drug delivery, [18] disease diagnosis, [19] and photothermal therapy of cancer. [20] Clearly,the use of MIPs as cancer therapeutic agents is still at av ery early stage and further evidence of inhibiting cancer signaling pathways by MIPs are essential to promote the development of MIPs for cancer therapy.…”
Section: Inhibition Of Her2-positiveb Reast Cancer Growth By Blockingmentioning
confidence: 99%
“…According to the boronate-affinity-controllable oriented surface imprinting approach, the thickness of the imprinting layer was directly proportional to the imprinting time. [20] According to the estimated length of the glycans (Supporting Information, Figure S1), we optimized the imprinting by setting the polymerization time at 40, 50, 60, and 70 min and evaluated the imprinting effect in terms of imprinting factor (IF). TheIF value was calculated according to the ratio of the fluorescence…”
Section: Inhibition Of Her2-positiveb Reast Cancer Growth By Blockingmentioning
confidence: 99%
“…Nanoparticles of gold (AuNPs) are known to be a promising material in terms of their application in biomedicine as biosensors [1][2][3], biomarkers [4,5], and for bioimaging [6,7], drug delivery [8,9] etc. Additionally, AuNPs deposited onto Si substrate exhibit surface plasmon resonance [10] which might help to improve overall catalytic property of Si-based materials and thereby enhance performances of devices based on such materials, e.g.…”
Section: Introductionmentioning
confidence: 99%